Tetrahedral framework nucleic acids promote scarless healing of cutaneous wounds via the AKT-signaling pathway - Zhu, Junyao (Signal Transduct Target Ther, 2020)
While the skin is considered the first line of defense in the human body, there are some vulnerabilities that render it susceptible to certain threats, which is an issue that is recognized by both patients and doctors. Cutaneous wound healing is a series of complex processes that involve many types of cells, such as fibroblasts and keratinocytes. This study showed that tetrahedral framework nucleic acids (tFNAs), a type of self-assembled nucleic-acid material, have the ability to promote keratinocyte(HaCaT cell line) and fibroblast(HSF cell line) proliferation and migration in vitro. In addition, tFNAs increased the secretion of vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) in HSF cells and reduced the production of tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β) in HaCaT cells by activating the AKT-signaling pathway. During in vivo experiments, tFNA treatments accelerated the healing process in skin wounds and decreased the development of scars, compared with the control treatment that did not use tFNAs. This is the first study to demonstrate that nanophase materials with the biological features of nucleic acids accelerate the healing of cutaneous wounds and reduce scarring, which indicates the potential application of tFNAs in skin tissue regeneration.